Socio-Spatial Conflicts, Justice, Resistance. Historical Preservation and Construction of Identities in Latin American Cities - de Jesus Peixoto Faria, Teresa; Musset, Alain (Geografares, 2017)
Socio-Spatial Conflicts, Justice, Resistance. Historical Preservation and Construction of Identities in Latin American Cities